1994
DOI: 10.1099/00221287-140-6-1395
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the oxygen affinities of terminal oxidases in Azotobacter vinelandii using the deoxygenation of oxyleghaemoglobin and oxymyoglobin: cytochrome bd is a low-affinity oxidase

Abstract: Azotobacter vinelandii is an obligately aerobic diazotrophic bacterium with two known terminal oxidases of the cytochrome o-and bd-types. The latter is required for respiratory protection of the oxygen-labile nitrogenase during aerotolerant nitrogen fixation. The apparent affinities (K,) for oxygen uptake by A. vinelandii cells and membranes respiring DL-malate have been determined by using the deoxygenation of oxyleghaemoglobin or oxymyoglobin as sensitive reporters of dissolved oxygen concentration. Dualwave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 24 publications
7
80
1
Order By: Relevance
“…In E. coli the induction of cytochrome bd occurs at low O 2 levels that are consistent with its high-oxygen affinity. In contrast, A. vinelandii induces cytochrome bd at high oxygen levels consistent with its lower oxygen affinity and a role in protective respiration under N 2 -fixing conditions (D'Mello et al, 1994;Moshiri et al, 1991b;Kelly et al, 1990). It is clear from our data that membranes of wild-type P. aeruginosa do not contain a spectrally detectable cytochrome d signal under high-or low-aeration conditions.…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…In E. coli the induction of cytochrome bd occurs at low O 2 levels that are consistent with its high-oxygen affinity. In contrast, A. vinelandii induces cytochrome bd at high oxygen levels consistent with its lower oxygen affinity and a role in protective respiration under N 2 -fixing conditions (D'Mello et al, 1994;Moshiri et al, 1991b;Kelly et al, 1990). It is clear from our data that membranes of wild-type P. aeruginosa do not contain a spectrally detectable cytochrome d signal under high-or low-aeration conditions.…”
Section: Discussionsupporting
confidence: 41%
“…The aerobic diazotroph Azotobacter vinelandii contains a spectrally similar cytochrome bd oxidase whose protein subunits show homology to E. coli CydA and CydB (Green et al, 1988;Moshiri et al, 1991a). However, the A. vinelandii cytochrome bd has a much lower O 2 affinity than the E. coli cytochrome bd (K m = 4.5 M;D'Mello et al, 1994), its expression increases at high O 2 tensions and it has a role in respiratory protection of nitrogenase (Kelly et al, 1990). A survey of bacteria that can perform cyanideinsensitive respiration (defined as respiration in the presence of 1 mM KCN) found that many bacteria contained spectrally detectable cytochrome bd (Akimenko and Trutko, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…This was achieved by using identical 250 ml flasks, shaking at 200 r.p.m., but altering the medium volume. The k L a values for medium volumes of 25 ml (high), 75 ml (medium), and 150 ml (low) were estimated by the sulphite oxidation method (Pirt, 1975;Ruchti et al, 1985;Gil et al, 1992;D'Mello et al, 1994). Fig.…”
Section: Methodsmentioning
confidence: 99%
“…A protective effect against oxygen toxicity was shown for the branched respiratory system in the bacterium Azotobacter¨inelandii, which possesses an extremely oxygen sensitive nitrogenase. In this case cytochrome d is used to deplete oxygen in Ž the vicinity of the enzyme Jones, 1977;Gottschalk, 1986;D'Mello et al, 1994;Bertsova . et al, 1997 …”
Section: Mitochondrial Mechanisms Behind Oxyconformitymentioning
confidence: 99%